2018
DOI: 10.3390/md16120495
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Collagen from Codfish Skin as a Biomaterial for Biomedical Applications

Abstract: Collagen is one of the most widely used biomaterials, not only due its biocompatibility, biodegradability and weak antigenic potential, but also due to its role in the structure and function of tissues. Searching for alternative collagen sources, the aim of this study was to extract collagen from the skin of codfish, previously obtained as a by-product of fish industrial plants, and characterize it regarding its use as a biomaterial for biomedical application, according to American Society for Testing and Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 63 publications
(80 reference statements)
11
66
0
2
Order By: Relevance
“…Equally important and regarding their great biotechnological potential, cod by-products can be established as alternative raw-materials for the production of biomolecules highly demanded by several industrial sectors. In particular, cod skin is a significant by-product generated when cod is processed as fillets and/or shredded, which could be utilized to produce collagen [5][6][7][8], often incorporated in the production of functional food or medicine due to its properties.…”
Section: Introductionmentioning
confidence: 99%
“…Equally important and regarding their great biotechnological potential, cod by-products can be established as alternative raw-materials for the production of biomolecules highly demanded by several industrial sectors. In particular, cod skin is a significant by-product generated when cod is processed as fillets and/or shredded, which could be utilized to produce collagen [5][6][7][8], often incorporated in the production of functional food or medicine due to its properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bovine spongiform encephalopathy (mad-cow disease) and foot-and-mouth disease (FMD) crisis as well as religious and social issues in some countries and markets and ecological impact of wasting the fish skin are the driving force for the increasing commercial use of fish collagen (Badii and Howell, 2006;Blanco et al, 2017;Ennaas et al, 2016;Gilsenan and Ross-Murphy, 2000;Karim and Bhat, 2009;Kim and Mendis, 2006;Rustad, 2003;Supavititpatana et al, 2008;Wasswa, et al, 2007). This approach assures the sustainable exploitation of marine resources whilst addressing the waste disposal issues related to environmental pollution (Carvalho et al, 2018). Recent research indicates that marine organisms are the most convenient and the safest sources to obtain high-quality collagen.…”
Section: Collagen and Gelatinmentioning
confidence: 99%
“…Some research works in Japan has demonstrated that fish scales of sardines have potential as an important collagen source (Belouafa et al, 2018;Kimura and Ohno, 1987;Nomura et al, 1996). Rohu, catla, megrim, dover sole, codfish, hake, carp, shark, spotted golden goatfish, tuna, niger triggerfish and tilapia are some of the fish species that have been subjected to extraction of collagen from marine vertebrates (Gómez-Guillén et al, 2002;Kittiphattanabawon et al, 2010;Matmaroh et al, 2011;Zhang et al, 2011;Carvalho et al, 2018). A recent study found that collagens extracted from Atlantic Salmon Salmo salar has the potential for use as scaffolds for bone tissue engineering applications (Bernhardt et al, 2018).…”
Section: Collagen and Gelatinmentioning
confidence: 99%
See 2 more Smart Citations